PARADIGMA PENAFSIRAN ALQURAN NUSANTARA (Analisis Tafsir Aceh ‘Tafsir Pase’) - Tamrin Talebe (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: This article discusses  Tafsīr Pase, a local exegesis of the Qur'an. The tafsīr was written in Aceh in pre independence day, brought about by the unstable social conditions (conflict). These conditions have implications on the pattern of this tafsīr, so that the contains cover the ideas on the empowerment of  Acehnese, expected to increase the unity and the brotherhood among them. Tafsīr Pase compiled by a team of five people. The name “Pase”, which is used as the name of this tafsīr, was  taken from one of the oldest kingdoms in Aceh. It is interesting that this quranic exegesis begins with the study of 'Ulūm al-Qur'ān before entering the discussion of tafsīr using cultural approach.Kata Kunci: Tafsir Pase, Aceh, pendekatan kebahasaan, sastra lokal